Smog chamber study of secondary organic aerosol formation from gas- and particle-phase naphthalene ozonolysis. (1st February 2023) - Liu, Jixing; Zhu, Shuping; Guo, Teng; Jia, Bin; Xu, Li; Chen, Jun; Cheng, Ping
Abstract: Naphthalene (Nap), one of the most abundant PAHs in the atmosphere, has been shown to be an important secondary organic aerosol (SOA) precursor. In this study, the gas- and particle-phases (Suspended Nap-coated polystyrene latex spheres (PSLs) generated by vaporization condensation) Nap ozonolysis were investigated in a 1000 L volume cubic Teflon smog chamber. Gas-phase products and Nap-SOAs were observed from the gas- and particle-phase Nap ozonolysis via homogeneous and heterogeneous reactions, respectively. The time-dependent size distribution and mass concentration of Nap-SOAs were analyzed using a scanning mobility particle sizer and a laboratory-developed single-particle aerosol mass spectrometry (SPAMS) instrument. The chemical components of the homogeneous and heterogeneous reaction products were analyzed on-line by single photo ionization mass spectrometry (SPIMS), SPAMS, as well as by thermal desorption gas chromatograph-mass spectrometry. The results showed that the chemical components of the gas-and particle-phase Nap ozonolysis were essentially the same, with the dominant products being phthalaldehyde, phthalic anhydride, 2-carboxybenzaldehyde, and benzoic acid; Nap-SOA formation was attributed to the formation of new particles as well as the uptake of homogeneous and heterogeneous Nap oxidation products on the gas-phase or/and the particle surface. Based on the online measurement results, the reaction mechanism of Nap-ozonolysis also exhibits an initial carbon atom or double-bond attacks by O3, and kinetic analysis of Nap-coated PSLs ozonolysis shows a heterogeneous reaction rate constant of 2.55E-4 s −1 with R 2  = 0.984. This study provides a systematic approach to characterize the chemical and physical properties of the gas- and particle-phase Nap ozonolysis in real time, which will deepen our understanding of the migration and transformation of PAHs in the atmosphere. Highlights: Gas- and particle-phases Nap ozonolysis were investigated in a smog chamber. Gas-phase products and Nap-SOAs were observed via homogeneous and heterogeneous reactions. Nap-ozonolysis reaction mechanism exhibits an initial carbon atom or double-bond attacks by O3 . Nap-coated PSLs ozonolysis shows a heterogeneous reaction rate constant of 2.55E-4 s −1 with R 2  = 0.984.